Quality and content evaluation of thyroid eye disease treatment information on TikTok and Bilibili - Haisheng Wang; Huahong Zhang; Jiamin Cao; Feng Zhang; Wei Xiong (Scientific Reports)
Abstract Thyroid eye disease (TED) is an autoimmune condition that commonly impacts patients’ visual function, appearance, and psychological well-being. Challenges in TED management include low early detection rates and large variation in treatment response. Video platforms like TikTok and Bilibili are increasingly utilized for health information dissemination, yet the quality of TED treatment content on these platforms varies significantly. This cross-sectional study collected videos on “甲亢突眼的治疗” from TikTok and Bilibili in March 2025. After applying exclusion criteria, 152 videos (89 from TikTok, 63 from Bilibili) were analyzed. Quality, reliability, and educational value were assessed using the Global Quality Score (GQS), modified DISCERN (mDISCERN), Patient Education Materials Assessment Tool (PEMAT), and Journal of the American Medical Association (JAMA) benchmark criteria. Additionally, the study analyzed video content integrity, uploader identity, and the correlation with user interaction data. TikTok videos scored higher in quality (GQS: 3.00 ± 0.58; mDISCERN: 3.17 ± 0.73) compared to Bilibili (GQS: 2.65 ± 0.65; mDISCERN: 2.21 ± 0.88; p < 0.001). On Bilibili, 62% of videos were uploaded by Traditional Chinese Medicine (TCM) physicians, yet these scored lower in quality. Professionally uploaded content, particularly by ophthalmologists, outperformed non-professional videos (e.g., patient). However, the video interaction metrics uploaded by patients showed better performance. In terms of content, only 27% addressed staged treatment, and 11.8% mentioned risk factor control. Correlation analysis revealed strong correlations between interaction data, but interaction data have no correlation with GQS, mDISCERN, and PEMAT scores. Short video platforms exhibit a dual role in the dissemination of TED treatment information: enhancing public awareness of diseases through professional content while risking misinformation due to inadequate auditing. Recommended interventions include robust platform certification, active involvement of medical organizations in content creation, and public education on prioritizing verified sources.